Plan estratégico para el mejoramiento de los servicios educativos del área técnica de la unidad educativa La Maná, cantón La Maná, Año 2014-2018. - Guaranda Shigui, Liseth Patricia (2015)
Every day is necessary to have a plan not only for businesses but also for educational institutions, since it is an effective tool for processes that impact favorably on any big or small business. It is convinced that if you use this tool you will get favorable results both internally, because it takes all for one way, and externally because they are gradually seeing the results of change. For these reasons, the research aims to develop a strategic plan for the improvement of the Technical Department of the Education Unit La Mana, which has no proper planning, since it does not have a strategic plan. This research allows managers to understand the flaws and strengths that has the technical area, and is made with the intention of improving the daily activities of all the members, as it is important to continue improving every day, with the help of a planning sought to achieve quality services. It is necessary and important that all institutions have a strategic plan, as this is what will lead all by a single goal, and the Technical Department of the Education Unit The Mana can not stay behind, so this research aims to be a contribution to the improvement of educational services.